Baicalin regulates stem cells as a creative point in the treatment of climacteric syndrome - Wei, Qian; Hao, Xia; Lau, Benson Wui-Man; Wang, Shaoxia; Li, Yue (Frontiers in Pharmacology, 2022)
It is widely acknowledged that the climacteric syndrome negatively affects women’s quality of life and leads to cerebral ischemic injury, osteoporosis and cardiovascular disease. One of the main active ingredients in Radix Scutellariae, Baicalin, has been established to possess a wide range of pharmacological effects and is beneficial in enhancing osteogenic differentiation and cardiovascular disease. Baicalin’s profound metabolic impact on various stem cell populations and their fate specification could improve the efficiency of stem cell therapy for climacteric syndrome. However, Baicalin-mediated processes are complex and many of the underlying mechanisms are not fully fathomed yet. This review aims to shed light on the regulatory role of Baicalin on the diverse behaviors of distinct stem cell populations and provide a good cell source for stem cell therapy to broaden the therapeutic landscape for climacteric syndrome patients.